Los colaboradores del banco de la nación agencia 1 Trujillo tienen la resistencia a la adaptación al cambio del rol comercial - Baltodano Vásquez, Betsy Paola (2017)
ABSTRACT The present research work has the general objective of identifying the influence of resistance to change and the collaborators of the Bank of the nation within the commercial role. Due to the continuous changes that are generating in the work environment, Necessary to have more competitive entities. For this reason the present investigation a study of the problematic reality in order to find if there is any influence of the resistance to the change in the workers in the area of the commercial role; The methodology used is based on a survey, the same one that was applied to the collaborators of the Bank of the Nation - Agencia Trujillo. Finally, this research intends to be able to contribute in later investigations of studies similar to this one.